PWE-314 Efficacy and complications in the use of self-expanding colonic stents for large bowel obstruction at a single centre: an analysis of 13 years experience. (22nd June 2015) - Kershaw, EL; Orr, OE; Dudding, TC; Bryant, T; Knight, JS
Abstract : Introduction: Self-expandable metal stents (SEMS) may be used in patients presenting with large bowel obstruction (LBO) and offer a less invasive alternative to surgery and thus avoid the potential need for a stoma. Method: A retrospective analysis of all patients who underwent attempted SEMS placement for LBO between 2001 and 2014 at a university teaching hospital. Patients were identified from the radiology database and hospital coding via the hospital's informatics system. Results: Over the 13-year review period, a primary SEMS was attempted in 143 patients, median age 72 (range 25–108) years, sex ratio 83 males: 60 females. Indications for SEMS were palliative treatment of colorectal cancer (CRC) 101; as bridging prior to resectional surgery for CRC 14; extrinsic compression in 19 and for benign disease in 8 patients. SEMS placement was successful in 110 (77%) patients: in 83 (82%) palliative; 13 (93%) bridging; 12 (63%) compression and 2 (25%) benign groups. 85% of SEMS were placed in the distal colon. In the bridged patients 54% did not require a stoma at subsequent surgery. 91(83%) patients successfully stented had no complication. Of the complications that occurred, 13(15.7%) occurred in palliative, 3(23.1%) bridging, and 3(25%) compression groups. Early complications (<48hrs) occurred in 8 patients: 3 perforations; 4 failures to open; 1 migration and 1 PR bleed. There was 1 death and 7 proceeded to surgery. There were 6 late complications (<1 month): 5 perforations and 1 reobstruction, of which there were 2 deaths and 4 had surgery. Delayed complications (>1 month) occurred in 4 patients, 3 required surgery. Overall median survival post SEMS was 212 days. According to indication for SEMS, 30- and 90-day survival was respectively: palliative 81.2% and 68.2%; bridging 92.3%; compressive 50% and 33.3% and benign 100%. Median (IQR) survival was: palliative 205 (49–425); bridging 766 (408–960) and compression 27 (12–158) days. Conclusion: The commonest indication for SEMS placement was malignant LBO from CRC. In palliative patients it has a good success rate and avoids the need for surgery in patients with a limited median survival. As a bridge to surgery in patients undergoing subsequent surgery it has a high success rate but does not always avoid the need for a stoma. Disclosure of interest: None Declared.